Climate Change-Related Distress Within the Dominant Mental Health Paradigm: Problems, Pitfalls, and a Possible Way Forward - Rana R. Kökçinar (Psychotherapy and Counselling Journal of Australia)
Climate change-related distress (CCRD) is a salient discourse, with contemporary resources for addressing CCRD currently dominated by positivist ideology. Such resources are problematic as they instil individualistic notions of behaviour change to combat climate change and CCRD, oversimplifying the problem and shifting focus away from systemic power imbalances and injustices that overwhelmingly contribute to climate change and CCRD. Addressing CCRD should involve a shift from an individualistic focus to collaborative conversations and frameworks that have the capacity to consider inherently complex issues of cultural and epistemological diversity. One such framework that incorporates non-pathologising understandings of CCRD is the Power Threat Meaning Framework (PTMF). Critical use of the PTMF to describe and support experiences of CCRD can be relevant for marginalised communities as it centres political, social, and relational contexts and assists in the cocreation of meaningful narratives while addressing systemic power imbalances and injustices, thus making way for collective action and empowerment processes for marginalised communities disproportionately affected by anthropogenic climate change.